METODE ITERASI JACOBI DAN GAUSS-SEIDEL PREKONDISI UNTUK MENYELESAIKAN SISTEM PERSAMAN LINEAR DENGAN M-MATRIKS - Efriani Widya; Syamsudhuha '; Bustami ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the preconditioner for solving the linear system Ax = b, where A is of the form M-matrix, which is a review of the Zhuan-De Wang and Ting-Zhu Huang paper [Applied Mathematics Letters, 19 : 1029 − 1036 (2006)]. Numericalexperiments using some sizes of A show that the convergence rate of Jacobi and Gauss Seidel type methods can be increased using the preconditioner.